The Impact of Credit Diversification on Credit Risk and Performance of Indonesian Banks - Iin Emy Prastiwi; Anik Anik (Global Review of Islamic Economics and Business, 2020)
This study aims to identify the effect of credit diversification in the economic sector on credit risk and performance of commercial banks in Indonesia. Multiple linear regression is used to determine the effect of credit diversification on credit risk and banking performance. The data used in this study is the aggregated financial statements of commercial banks inIndonesia during the 2015-2018. The results indicate that credit diversification based on the economic sector has a significant effect on increasing the profitability of commercial banks in Indonesia. The credit diversification based on the economic sector also has a significant effect in reducing credit risk. Two control variables, namely company size and banking liquidity have a significant negative effect on profitability respectively. In the case of credit risk, the company size hasapositive effect, while the banking liquidity has no effect. These findings support the traditional banking theory which states that banks that diversify their credit portfolios can reduce the credit risk and increase profitability.